Embracing Global Computing in Emerging Economies First Workshop, EGC 2015, Almaty, Kazakhstan, February 26-28, 2015. Proceedings - Horne, Ross.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the First Workshop on Embracing Global Computing in Emerging Economies, EGC 2015, held in Almaty, Kazakhstan, in February 2015. The 13 revised full papers presented were carefully reviewed and selected from 28 submissions. The papers focus on the topic in two ways: one part is directly relevant to the problems of delivering cloud services in an emerging economy such as Kazakhstan, the other part represents ICT innovation by scientists of the region.
Keywords: Application software; Computer communication systems; Computer Applications; Computer Communication Networks